Experimental and analytical investigation on the nonlinear behaviors of glulam moment-resisting joints composed of inclined self-tapping screws with steel side plates. Issue 15 (November 2019) - Komatsu, Kohei; Teng, Qicheng; Li, Zherui; Zhang, Xiaolan; Que, Zeli
Glulam moment-resisting joint composed of inclined self-tapping screws with steel side plates were designed and its nonlinear moment-rotational skeleton curve was predicted by taking nonlinear load ( P )–deformation ( u ) relationships of all moment-resisting components into considerations within step-wise linear calculation process. P-u relationships of all moment-resisting components were estimated by the fundamental shear joint tests or appropriate empirical relationships, and they were approximated by the tetra polygonal line curves or bi-linear curves. The extended Normalized Characteristic Loop model, which was originally developed for reinforced concrete construction, was applied to describe the hysteresis loops. For predicting failure load, the design equations for a mechanical joint loaded with inclination to the grain direction were applied. Three replications of T-shaped beam-column joint specimens were fabricated using Canadian spruce glulam beam and column. Connections of steel plates to glulam members were all composed of full-threaded inclined self-tapping screws. Static push-pull cyclic loading tests were conducted and observed behaviors were compared with step-wise linear analytical results. Agreements between predicted nonlinear behaviors and observed ones were good on the whole.